2018
DOI: 10.3311/ppme.10622
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MHD on Nanofluid flow, Heat and Mass Transfer over a Stretching Surface Embedded in a Porous Medium

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Yahiaoui et al [13] reported the investigation of the mixed convection from a confined rotating circular cylinder. Mami and Bouaziz [14] considered the effect of MHD on nanofluid flow, heat and mass transfer over a stretching surface embedded in a porous medium. Venkateswarlu et al [15] presented the thermodynamic analysis of Hall current and Soret number on hydromagnetic couette flow in a rotating system with a convective boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Yahiaoui et al [13] reported the investigation of the mixed convection from a confined rotating circular cylinder. Mami and Bouaziz [14] considered the effect of MHD on nanofluid flow, heat and mass transfer over a stretching surface embedded in a porous medium. Venkateswarlu et al [15] presented the thermodynamic analysis of Hall current and Soret number on hydromagnetic couette flow in a rotating system with a convective boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that slip parameter works as a catalyst for skin‐friction coefficient. Mami and Bouaziz 20 studied convection boundary layer flow over stretching surface in porous media and magnetic fluid. Raju et al 21 discussed the flow of nanoliquid influenced by thermal radiation over a cone.…”
Section: Introductionmentioning
confidence: 99%